Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise - Filho Teixeira, José; Damesin, Claire; Rambal, Serge; Joffre, Richard (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements
Keywords: Arbutus unedo; mixed Mediterranean woodland; Penman-Monteith equation; Quercus ilex; Quercus pubescens; sap flow; stomatal and canopy conductances

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements